ISDE Presidential Biography: David B. Skinner, MD. Issue 10 (13th December 2019) - Ferguson, M K
SUMMARY: Dr. David Skinner, the 4th President of the ISDE, was a world-renowned surgeon, educator, scholar, and leader. He participated in the formation of the ISDE, hosted two international congresses in 1983 and 1989, and made important advances in the ISDE during his presidential tenure 1992–1995.